Three new species of quill mites (Acari: Syringophilidae) parasitizing the wrens (Aves: Troglodytidae) - Sikora, Bozena; Fajfer, Monika; Kavetska, Katarzyna; Skoracki, Maciej (Zootaxa, 2012)
Three new species of syringophilid mites (Acari: Prostigmata: Cheyletoidea) associated with birds of the family Troglo-dytidae (Aves: Passeriformes) are described: Syringophiloidus microcerculus Sikora & Skoracki sp. nov. from Microcer-culus marginatus (Sclater) from Brasil, Aulonastus henicorhina Sikora & Skoracki sp. nov. from Henicorhina leucosticta(Cabanis) from Ecuador, and Picobia troglodytidus Sikora & Skoracki sp. nov. from Henicorhina leucophrys (Tschudi) from Costa Rica.